Seismic Performance of Various Piles Considering Soil–Pile Interaction under Lateral Cycle Loads for Integral Abutment Jointless Bridges (IAJBs) - Fuyun Huang; Yulin Shan; Ahad Javanmardi; Xiaoye Luo; Baochun Chen (Applied Sciences, 2020)
The flexural pile foundation is used in integral abutment jointless bridges (IAJBs) in practical engineering to effectively dissipate the horizontal reciprocating deformation induced by the ambient temperature or earthquake loadings. Various types of flexural piles including the H-shaped steel pile (HP), prestressed concrete pile (PC), prestressed high-strength concrete pile (PHC) as well as the reinforcement concrete pile (RC) have been implemented in IAJBs. However, there is a lack of comprehensive studies on the flexural deformation and seismic performances of these piles. In order to investigate and compare their mechanical behaviors and seismic performances, a low-cycle pseudo-static test on several different types of piles was carried out. The test results indicated that the plastic hinge location of piles moved to a deeper pile depth with the increase of reinforcement ratio, buried pile depth and prestressing level, which led to better pile–soil interaction. The crack resistance of a concrete pile was improved as the reinforcement ratio and prestressing level increased. Moreover, the rectangular pile had a better soil–pile interaction and energy dissipation capacity than the circular pile. The inflection point of the pile deformation shifted deeper as reinforcement ratio, buried pile depth and prestressing level increased, which improved the effective length and horizontal deformation capacity of piles. The H-shaped steel pile showed a better elastic-plastic deformation capacity, ductility and energy dissipation capacity as compared to the concrete pile. Moreover, the pile having a higher bearing ratio sustained larger lateral loads whereas the surrounding soil was subjected to higher loads. Finally, new seismic design criteria of three-stage seismic fortification and five damage level for the concrete piles of IAJBs were proposed.